Papua New Guinea agri-food trade trends: Dietary change and obesity - Schmidt, Emily; Fang, Peixun (International Food Policy Research Institute, 2021)
The onset of the COVID-19 pandemic has presented a unique challenge to governments across the globe, reinforcing the need to improve understanding of domestic and international trade trends to provide more informed options for response. During the last several months, IFPRI has been analyzing a variety of Papua New Guinea (PNG) national and global datasets with the goal of expanding analytical tools to evaluate potential production shortfalls and food price shocks, and their associated impacts on household food security and livelihoods. This research focuses on agri-food import and export trends during the last two decades to better evaluate potential changes in related import demand and export potential in PNG. In doing so, this research informs an upcoming economy-wide multi market model analysis that will model a variety of potential shocks to household welfare to identify policies to manage potential ensuing food security threats. PNG’s growth in international agri-food trade (both export and import) will continue to be important to overall food security outcomes among rural and urban households. Rural households that produce key export cash-crops (e.g., coffee, cocoa, palm oil) depend on the cash economy to supplement overall food consumption, while urban households depend on rice and other agri-food imports (as well as domestic goods) for consumption. Agri-food imports are also contributing to important increases in the availability of protein-dense foods, with the value of poultry imports growing, on average, 30 percent per capita per year from 2001 – 2016. Although PNG’s agri-food import data suggest a greater demand for higher value food items such as animal-sourced foods, the total import value of ultra-processed foods, such as sugary drinks, are also increasing rapidly within PNG. The profitability and growth of agricultural exports and imports are driven by several factors, including levels of public investment in infrastructure, weather and climate shocks, security and political stability, and conditions in the world market. Government economic policies, including exchange rate, trade and price policies, also heavily influence agricultural trade. to promote and facilitate domestic movement of goods, as well as macro-economic policies that influence the relative price of tradable to non-tradable goods (the real exchange rate) should be managed appropriately to support and incentivize greater agri-food production and trade. These policies could also be paired with an expanded set of education programs that integrate nutrition-sensitive information to address current increases in demand and consumption of high-saturated and sugary processed goods, of which total import values are rapidly increasing in PNG. Finally, a greater portfolio of organized databases, analytical tools and resources are warranted to facilitate real-time analysis that can inform key development investments and initiatives.